A concerted action of Hepatitis C virus P7 and nonstructural protein 2 regulates core localization at the endoplasmic reticulum and virus assembly - Boson, Bertrand; Granio, Ophélia; Bartenschlager, Ralf; Cosset, François-Loïc (PLoS pathogens, 2011)
Hepatitis C virus (HCV) assembly remains a poorly understood process. Lipid droplets (LDs) are thought to act as platforms for the assembly of viral components. The JFH1 HCV strain replicates and assembles in association with LD-associated membranes, around which viral core protein is predominantly detected. In contrast, despite its intrinsic capacity to localize to LDs when expressed individually, we found that the core protein of the high-titer Jc1 recombinant virus was hardly detected on LDs of cell culture-grown HCV (HCVcc)-infected cells, but was mainly localized at endoplasmic reticulum (ER) membranes where it colocalized with the HCV envelope glycoproteins. Furthermore, high-titer cell culture-adapted JFH1 virus, obtained after long-term culture in Huh7.5 cells, exhibited an ER-localized core in contrast to non-adapted JFH1 virus, strengthening the hypothesis that ER localization of core is required for efficient HCV assembly. Our results further indicate that p7 and NS2 are HCV strain-specific factors that govern the recruitment of core protein from LDs to ER assembly sites. Indeed, using expression constructs and HCVcc recombinant genomes, we found that p7 is sufficient to induce core localization at the ER, independently of its ion-channel activity. Importantly, the combined expression of JFH1 or Jc1 p7 and NS2 induced the same differential core subcellular localization detected in JFH1- vs. Jc1-infected cells. Finally, results obtained by expressing p7-NS2 chimeras between either virus type indicated that compatibilities between the p7 and the first NS2 trans-membrane domains is required to induce core-ER localization and assembly of extra- and intra-cellular infectious viral particles. In conclusion, we identified p7 and NS2 as key determinants governing the subcellular localization of HCV core to LDs vs. ER and required for initiation of the early steps of virus assembly.
Gesehen am 02.06.2022